Kleine Schriften zur Hellenistisch-Romischen Philosophie - Görler, Woldemar. (Philosophia Antiqua, 2004)
This book presents 17 articles by Woldemar Görler, published during the last 25 years, some of them not easily accessible hitherto. Most of them treat details of the history of the Hellenistic Academy and Cicero. Other papers explore the aftermath of Hellenistic thought in Lucilius, Lucretius, and Seneca, the literary form of Roman philosophical treatises, and Cicero's personal interpretation of Academic scepticism. All contributions are based on close reading of the source material. No attempt is made to harmonize conflicting evidence. Instead, different stages of the school discussions and some gradual changes in philosophical doctrine emerge more clearly. Special attention is paid to the conversion of Greek terms into Latin, in some cases implying unexpected consequences in meaning.